An industry test for ethnic discrimination in major league soccer. Issue 16 (20th September 2019) - Kerr, Craig
ABSTRACT: This paper tests for salary discrimination based on player ethnicity in Major League Soccer (MLS) by making innovative use of player movements in a unique setting. The discriminating team investigated is Club Deportivo Chivas USA, which had a preference for employing Hispanic players. Evidence of discrimination is found by analyzing how other teams valued the former players of Chivas USA differently across ethnicity after the team was disbanded by the league. The nature of MLS player contracts and drafting rules allow for a simple and unique test for salary discrimination that has not previously been possible to implement.